1978
DOI: 10.3109/10826087809039318
|View full text |Cite
|
Sign up to set email alerts
|

The Drug Use Index: A Measure of the Extent of Polydrug Usage

Abstract: A drug use index (DUI) is constructed from actual usage data of 1,121 respondents (517 males and 604 females). It is proposed that this index represents a quantitative measure of the degree of involvement in polydrug use. Correlations between the DUI and use of 19 drugs or drug classes are reported. Furthermore, some applications of the DUI are demonstrated with specific reference to four psycho-personality tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Early research into the drug consumption patterns of young adults found that “multiple drug use” (Cohen, 1981; Single, Kandel, & Faust, 1974; Simpson & Sells, 1974) was prevalent. 1 Studies were initially designed to evaluate heroin addiction but as marijuana became increasingly identified as central to the drug problem, research on polydrug use gradually evolved to include non-opiate drugs (Sample, 1977; Douglass & Khavari, 1978). The significance of marijuana, alcohol, and tobacco in this research has been inconsistent.…”
Section: Clarifying the Meanings Of Polydrug Usementioning
confidence: 99%
“…Early research into the drug consumption patterns of young adults found that “multiple drug use” (Cohen, 1981; Single, Kandel, & Faust, 1974; Simpson & Sells, 1974) was prevalent. 1 Studies were initially designed to evaluate heroin addiction but as marijuana became increasingly identified as central to the drug problem, research on polydrug use gradually evolved to include non-opiate drugs (Sample, 1977; Douglass & Khavari, 1978). The significance of marijuana, alcohol, and tobacco in this research has been inconsistent.…”
Section: Clarifying the Meanings Of Polydrug Usementioning
confidence: 99%
“…In one study, ratio-level items inquiring about current drug use were collected from a sample of high school students. In the second study, ordinal-level current drug-use data published by Douglass and Khavari (1978) were analyzed.…”
Section: Two Studies Of Current Drug Usementioning
confidence: 99%
“…Polydrug use gained a foothold and growing recognition among researchers several decades ago [1,2], and currently there is an increasing body of research literature in this regard [3]. According to the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA), polydrug use has become a dominant pattern of drug use in Europe [4] and it has been brought up as a challenge in the formulation of the EU Drugs Strategy (2013-2020) [5].…”
Section: Introductionmentioning
confidence: 99%